Characteristics of the level of psychomotor abilities of female handball players - Sliz, M.; Przednowek, K. H.; Kapuscinski, P.; Dziadek, P.; Godek, L.; Warchol, K.; Zielinski, J.; Przednowek, K. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background Handball is a high-intensity game, during which players run, change directions with or without the ball, interact with the opponent and make different decisions in both offensive and defensive actions. Players` performance may depend on a number of factors, including explosive force, power, speed and agility. Players` results may be significantly influenced by their, psychomotor abilities. This article presents an analysis of selected psychomotor abilities of female handball players at different level of competition.